Implementation of Learning of Vocal Processing Techniques Using The NHT Model in SD Negeri 10 Lut Tawar Aceh Central - Aida Fitri; Suci Fitriani (Universitas Syiah Kuala, 2022)
The learning model is a plan or pattern that can be used to desaign learning, materials, and guide learning the classroom. This study aims to describe the implementation of vocal technique learning using the NHT model fourth grade of SD Negeri 10 central Aceh. This research approach is qualitative with descriptive type. Data collection techniques by observation, interviews. Data analysis technique is done by data reduction, data presentation, data verification. Based on research data that the implementation of learning technique using the NHT model has been going well. The use of the NHT model when learning motivates students in learning vocals processing techniques. Students are divided in to several groups and given assignments as ccording to initials or number. Each groups completes its task and presents the result of the task. They can also demonstrate in the form of singing practise by applying the corect vocal techniques. Keywords: Learning, NHT Model, Vocal Processing